Analysis Of The Factors Determining Job Satisfaction, Motivation, And Discipline On Employee Performance With Job Loyalty As An Intervening Variable - Bulan Rahma Watik,; Sutrisno,; Sumastuti, Efriyani (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze job satisfaction, motivation and discipline on employee performance with work loyalty as an intervening variable on employees of Universitas PGRI Semarang. The research method used is quantitative using Structural Equation Modeling (SEM) through AMOS software. The method used by researchers in selecting research samples is purposive sampling with a sample size of 132 employees. The results of this study indicate that the results of the study indicate that motivation and work discipline have a significant effect on work loyalty. In addition, work loyalty has a positive effect on employee performance and is able to mediate the influence of job satisfaction, motivation, and work discipline on employee performance. The second, third, fourth, seventh, seventh, ninth, and accepted hypotheses, while the first, fifth, and sixth hypotheses are rejected. Overall, the results of this study provide evidence that motivation, work discipline, and work loyalty have a significant effect on employee performance, and show a mediating effect of work loyalty.